EXOTIC CARBON SYSTEMS IN TWO-NEUTRON HALO THREE-BODY MODELS - Tomio, Lauro [UNESP]; Delfino, Antonio; Frederico, Tobias; Hadizadeh, M. R. [UNESP]; Yamashita, Marcelo Takeshi [UNESP]; Marques de Carvalho, Raquel S. (World Scientific Publ Co Pte Ltd, 2011)
The general properties of exotic carbon systems, considered as a core with a two-neutron (n - n) halo, are described within a renormalized zero-range three-body model. In particular, it is addressed the cases with a core of (18)C and (20)C. In such a three-body framework, (20)C has a bound subsystem ((19)C), whereas (22)C has a Borromean structure with all subsystems unbound. (22)C is also known as the heaviest:, carbon halo nucleus discovered. The spatial distributions of such weakly-bound three-body systems are studied in terms of a universal scaling function, which depends on the mass ratio of the particles, as well as on the nature of the subsystems.
Keywords: Halo nuclei; Binding Energies; Faddeev Equation; Three-body Systems